Benzimidazole based Pt(ii) complexes with better normal cell viability than cisplatin: synthesis, substitution behavior, cytotoxicity, DNA binding and DFT study. Issue 80 (12th August 2016) - Mitra, Ishani; Mukherjee, Subhajit; Reddy B., Venkata P.; Dasgupta, Subrata; Bose K, Jagadeesh C.; Mukherjee, Sandip; Linert, Wolfgang; Moi, Sankar Ch.
Abstract : Water soluble Pt(ii ) complexes with higher viability towards normal cells and comparable cytotoxicity to cancer cells as compared to cisplatin. Abstract : cis -[Pt(ambim)Cl2 ]1 (where, ambim = 2-aminomethylbenzimidazole) has been synthesized and characterized by spectroscopic methods. Reaction kinetics between the hydrolyzed product, cis -[Pt(ambim)(H2 O)2 ] 2+ 2 withdl -penicillamine (dl -pen) and glutathione (GSH) have been studied spectrophotometrically in aqueous medium. At pH 4.0, the interactions of2 with the ligands show two distinct consecutive steps. The association equilibrium constant ( K E ) for the outer sphere complex formation and rate constants for both the steps have been evaluated. Activation parameters (Δ H ‡ and Δ S ‡ ) were evaluated using the Eyring equation and an associative mechanism is proposed for both the reactions. Computational studies using Density Functional Theory (DFT) were carried out to investigate the electronic structures of the complexes. To study the nature of the electronic transitions in complex1, time dependent DFT was performed. The DNA binding properties of the complexes2–4 were evaluated by spectroscopic titration, fluorescence indicator displacement experiments and electrophoresis measurements. The complexes effectively bind to calf-thymus DNA via different binding modes with intrinsic binding constants ( K b ) in the range of 2.22 × 10 4 to 4.76 × 10 4 M −1 which was supported by molecular docking studies. The antiproliferative properties of2–4 were probed in vitro against human cervical cancer, non-small cell lung carcinoma and hepatocellular liver carcinoma cell lines and2 was found to be most effective in growth inhibition in all the cell lines. Remarkably, the complexes also generate lower levels of reactive oxygen species (ROS) than cisplatin and have almost no adverse effects on normal cells.